(untitled) (Research, Society and Development, 2022)
Obesity is a chronic disease defined by the abnormal or excessive accumulation of fat that causes damage to health, characterized by a body mass index or BMI equal to or above 30. Seduced by the deceptive promise of rapid weight loss and without much effort, people choose to use drugs to lose weight in order to achieve a “perfect body” without effort and without any medical advice, making the indiscriminate use of anorectics. The objective of this study will be to describe the consequences caused by self-medication with anorectic drugs by obese individuals. It is an integrative literature review, a research technique that gathers and synthesizes relevant publications on a delimited topic or issue, in a systematic and orderly way, contributing to the deepening of the knowledge of the investigated topic, making it possible to draw conclusions about an area particular study, with a qualitative nature and temporality with cross-sectional data collection, the method for bibliographic survey consisted of research based on articles on obesity and its treatment, focusing on the adverse factors described in these studies, the search was carried out in the following bases of scientific data: Medline, SciELO, PubMed, Google Scholar, Lilacs. However, society’s awareness of the consequences of self-measurement of these drugs must be performed routinely, as well as guidance on the use of these drugs, since the risks of indiscriminate consumption, without medical and pharmaceutical monitoring of anorectics, are many and can lead to various complications for physical health such as tachycardia, high blood pressure, insomnia, irritability.